Antidiabetic Activity of Gnidia glauca and Dioscorea bulbifera: Potent Amylase and Glucosidase Inhibitors. (9th July 2011) - Ghosh, Sougata; Ahire, Mehul; Patil, Sumersing; Jabgunde, Amit; Bhat Dusane, Meenakshi; Joshi, Bimba N.; Pardesi, Karishma; Jachak, Sanjay; Dhavale, Dilip D.; Chopade, Balu A.
Abstract : Diabetes is a metabolic disorder affecting about 220 million people worldwide. One of the most critical complications of diabetes is post-prandial hyper-glycemia (PPHG). Glucosidase inhibitor and α -amylase inhibitors are class of compounds that help in managing PPHG. Low-cost herbal treatment is recommended due to their lesser side effect for treatment of diabetes. Two plants with significant traditional therapeutic potential, namely, Gnidia glauca and Dioscorea bulbifera, were tested for their efficiency to inhibit α -amylase and α -glucosidase. Stem, leaf, and flower of G. glauca and bulb of D. bulbifera were sequentially extracted with petroleum ether, ethyl acetate, and methanol as well as separately with 70% ethanol. Petroleum ether extract of flower of G. glauca was found to inhibit α -amylase significantly (78.56%). Extracts were further tested against crude murine pancreatic, small intestinal, and liver glucosidase enzyme which revealed excellent inhibitory properties. α -glucosidase inhibition provided a strong in vitro evidence for confirmation of both G. glauca and D. bulbifera as excellent antidiabetic remedy. This is the first report of its kind that provides a strong biochemical basis for management of type II diabetes using G. glauca and D. bulbifera . These results provide intense rationale for further in vivo and clinical study.